Closing the Loop on the GABA Shunt in Plants: Are GABA metabolism and signaling entwined? - Michaeli, Simon; Fromm, Hillel (Frontiers in Plant Science, 2015)
γ-Aminobutyric acid (GABA) is a non-proteinogenic amino acid that is found in uni- and multi-cellular organisms and is involved in many aspects of plant life cycle. GABA metabolism occurs by the action of evolutionary conserved enzymes that constitute the GABA shunt, bypassing two steps of the TCA cycle. The central position of GABA in the interface between plant carbon and nitrogen metabolism is well established. In parallel, there is evidence to support a role for GABA as a signaling molecule in plants. Here we cover some of the recent findings on GABA metabolism and signaling in plants and further suggest that both the metabolic and signaling aspects of GABA may actually be inseparable.